The patient experience of intensive care: A meta-synthesis of Nordic studies. Issue 8 (August 2015) - Egerod, Ingrid; Bergbom, Ingegerd; Lindahl, Berit; Henricson, Maria; Granberg-Axell, Anetth; Storli, Sissel Lisa
Abstract Background Sedation practices in the intensive care unit have evolved from deep sedation and paralysis toward lighter sedation and better pain management. The new paradigm of sedation has enabled early mobilization and optimized mechanical ventilator weaning. Intensive care units in the Nordic countries have been particularly close to goals of lighter or no sedation and a more humane approach to intensive care. Objectives The aim of our study was to systematically review and reinterpret newer Nordic studies of the patient experience of intensive care to obtain a contemporary description of human suffering during life-threatening illness. Design We conducted a meta-synthesis in which we collected, assessed, and analyzed published qualitative studies with the goal of synthesizing these findings into a new whole. Analysis was based on the scientific approach of Gadamerian hermeneutics. Settings Nordic intensive care units. Participants Patients in Nordic intensive care units. Methods We performed a literature search of qualitative studies of the patient experience of intensive care based on Nordic publications in 2000–2013. We searched the following databases: PubMed, CINAHL, Scopus, and PsycINFO. Each original paper was assessed by all authors using the Critical Appraisal Skills Program instrument for qualitative research. We included 22 studies, all of which provided direct patient quotes. Results The overarching theme was identified as: The patient experience when existence itself is at stake. We constructed an organizing framework for analysis using the main perspectives represented in the included studies: body, mind, relationships, and ICU-environment. Final analysis and interpretation resulted in the unfolding of four themes: existing in liminality, existing in unboundedness, existing in mystery, and existing on the threshold. Conclusions Our main finding was that human suffering during intensive care is still evident although sedation is lighter and the environment is more humane. Our interpretation suggested that patients with life-threatening illness descend into a liminal state, where they face the choice of life or death. Caring nurses and family members play an important role in assisting the patient to transition back to life.